Speaking Assessment Based On The 2013 Curriculum From English Teachers And Their Perception - Imro Atus Soliha (PROCEEDING UMSURABAYA, 2019)
This study was focused on the speaking assessment used by six English teachers at three Junior High School in Probolinggo. The objectives of this study are to explain; 1) the Implementation of Speaking Assessment based on 2013 Curriculum, 2) the types of speaking assessment from English teachers, and 3) teachers’ perception on speaking assessment based on 2013 curriculum. Type of this research was qualitative. The data were collected from interview, questionnaires, observation, and document analysis. The samples of this study were six English teachers who taught eight grade from three Junior High schools in Probolinggo. The data were classified and analyzed in qualitative way. The result showed that; 1) the English teachers of three Junior High Schools in probolinggo have applied the assessment in speaking, but not all standard was completed, 2) role play performance was used in assessing the students’ speaking skill, 3) teachers’ perception on speaking assessment was very good, and thought that the assessment could be the solution for  their problems in assessing student’s speaking skill.Keywords: assessment, speaking, curriculum 2013, perception.